Potret Kepatuhan Perpajakan Wajib Pajak Profesi Notaris - Su'adah, Su'adah; Faisol, Moh. (MONETER - JURNAL AKUNTANSI DAN KEUANGAN, 2024)
The notary profession is one of the professions that has a low level of compliance, which is ± 39% other than lawyers and curators. This study aims to determine the tax compliance of taxpayers who work as notaries, "MDMKN notaries". The research method used case studies by conducting interviews with three informants. The data is analyzed by data reduction, data presentation, conclusion, and verification and enhanced by data validity testing. The results of this study stated that notaries "MDMKN" obey and comply with tax rules and pay taxes and arrears. The compliance aspects that have been fulfilled include (1) compliance in registering as a taxpayer; (2) compliance with timely deposit of Period Tax Returns and Annual Tax Returns; (3) never been penalized for non-compliance with paying taxes; and (4) never make payment of tax arrears (STP/SKP) before maturity. Fulfillment of these tax obligations is one form of responsibility that must be fulfilled as a taxpayer who works as a notary. The implication of this research is that taxpayer awareness and level of knowledge about taxation are large assets in fulfilling tax compliance, so it is important for DJP to pay attention and grow taxpayer awareness and their understanding from an early age and for all circles.